METHOD FOR ADAPTIVE COHERENT COMPENSATION OF SIGNAL REFLECTED FROM CAR BODY - A. S. Heister (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Classification of ground vehicles is still actual task in radar systems due to its complexity. ISAR imaging of wheels and tracks of vehicles is effective way for vehicle classification. Signals reflected from vehicle body adversely affect the imaging procedure. Method for adaptive coherent compensation of signal reflected from car body is considered. The method is based on ISAR imaging of vehicle body, transformation of achieved image to temporal signal and its subtraction of received signal.